2021
DOI: 10.1111/are.15217
|View full text |Cite
|
Sign up to set email alerts
|

Substitution of fish meal with soybean meal for juvenile Chinese mitten crab ( Eriocheir sinensis ) reared at three salinities: Effects on survival, growth, antioxidant capacity and body composition

Abstract: A 60-day feeding experiment was conducted to evaluate the survival, growth, antioxidant capacity and body composition of the juvenile Chinese mitten crab (Eriocheir sinensis) reared at three salinities (0.5‰, 2‰ and 6‰) in response to the different substitution levels (0%, 24%, 39%, 57% and 100%) of fish meal (FM) by soybean meal (SBM). The five diets were named as S0, S24, S39, S57 and S100 respectively. Results showed that survival rate (SR) was only significantly affected by the substitution level at the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 45 publications
2
6
0
Order By: Relevance
“…The inhibition effect of intestinal digestive enzyme activities by replacing fishmeal with soybean meal in aquatic feed is a common phenomenon that has been well reported in previous studies. For instance, replacing 57% and 100% of fishmeal by soybean meal in Chinese mitten crab (Eriocheir sinensis) diets significantly reduced the intestinal digestive enzyme activities of trypsin, lipase, and amylase (Liu et al, 2021). Similar result was also reported by Zhang et al (2015) that replacing 12% to 48% fishmeal with soybean meal significantly decreased the intestinal lipase and amylase activities of rice filed eel (Monopterus albus).…”
Section: Apparent Digestibility and Digestive Enzyme Activitysupporting
confidence: 78%
See 2 more Smart Citations
“…The inhibition effect of intestinal digestive enzyme activities by replacing fishmeal with soybean meal in aquatic feed is a common phenomenon that has been well reported in previous studies. For instance, replacing 57% and 100% of fishmeal by soybean meal in Chinese mitten crab (Eriocheir sinensis) diets significantly reduced the intestinal digestive enzyme activities of trypsin, lipase, and amylase (Liu et al, 2021). Similar result was also reported by Zhang et al (2015) that replacing 12% to 48% fishmeal with soybean meal significantly decreased the intestinal lipase and amylase activities of rice filed eel (Monopterus albus).…”
Section: Apparent Digestibility and Digestive Enzyme Activitysupporting
confidence: 78%
“…Similar results were also observed in various species, such as European catfish (Silurus glanis) (Kumar et al, 2017), Tiger puffer (Takifugu rubripes) (Lim et al, 2011), sharpsnout seabream (Diplodus puntazzo) (Hernandez et al, 2007), red snapper (Lutjanus campechanus) (Davis et al, 2005), Pseudobagrus ussuriensis (Wang et al, 2016), stellate sturgeon (Acipenser stellatus) (Emdadi et al, 2013), Jian carp (Cyprinus carpio var. Jian) (Jiang et al, 2015b), rainbow trout (Oncorhynchus mykiss) (Harlioglu, 2011), Channa argus (Zhang et al, 2020), Epinephelus Fuscoguttatus (Liu et al, 2018), bullfrog (Rana catesbeiana) (Ding et al, 2019;Wang et al, 2020), and Chinese mitten carb (Eriocheir sinensis) (Liu et al, 2021). In this study, the increased FC with increasing dietary soybean meal indicated that supplementation of soybean meal decreased feed utilization; this may account for the depressed growth performance of shrimp.…”
Section: Growth Performancementioning
confidence: 99%
See 1 more Smart Citation
“…The detailed procedures can be found in the instructions of corresponding commercial kits. The unit definition can be referred in Liu, Wen, Man, et al (2021).…”
Section: Methodsmentioning
confidence: 99%
“…As one of the three main basins of the original distribution area of E. sinensis , Liaohe River Basin is characterized by the symbiotic culture model of rice crab with an annual yield amounting to 61,192 t in 2019 (Liu, Wen, Man, et al, 2021). According to the investigation, the salinity of water in Liaohe River Basin fluctuates between 2‰ and 6‰ (unpublished data).…”
Section: Introductionmentioning
confidence: 99%